The Effect of Accounting Training and Mentoring on SAK EMKM Compliance and MSME Business Performance - Tripalupi, Ramadhani Irma; Yulianti, Lina (Research Horizon, 2026)
Financial Accounting Standards for MSME are applicable to Indonesian MSMEs. However, preparing financial statements remains challenging due to limited accounting knowledge and the complexity of accounting processes. This study aims to examine the influence of accounting training with and without mentoring on the effectiveness of Financial Accounting Standards for MSME implementation and its implications for MSME business development. The research employed a quantitative experimental method involving halal MSME actors in Greater Bandung, divided into two groups: one receiving both training and mentoring, and the other receiving training only. Primary and secondary data were collected, and hypothesis testing was conducted using the Mann–Whitney test. Results indicate that accounting training combined with mentoring significantly improves the effectiveness of SAK EMKM implementation, with practical application limited to simple accounting and profit and loss reporting, and positively impacts business development through increased sales, profits, and customer numbers. Meanwhile, training without mentoring also affects SAK EMKM compliance, but its implications for business growth remain unclear. The study concludes that mentoring enhances the effectiveness of accounting training and supports MSME business development.